Ethical and Regulatory Concerns Regarding Potential Research Participants Who Are Justice Involved, But Not Incarcerated: Application of 45 CFR 46 Subpart C in the Healthy Brain and Child Development Study. - Cohen, Abagail D; Dawson, Liza; Johnson, Liza-Marie (American Journal of Bioethics, 2026)
The article focuses on the ethical and regulatory challenges of including justice-involved pregnant women, particularly those under court-ordered supervision but not incarcerated, in the HEALthy Brain and Child Development (HBCD) study. It examines the application of US federal regulations under 45 CFR 46 Subpart C, which provides additional protections for prisoners and similarly vulnerable populations, to participants who may be classified as "prisoners" despite not being in penal institutions. Commentaries emphasize the importance of including these women to address their and their children’s health needs while balancing protections against coercion and stigma, and recommend nuanced, context-sensitive approaches that respect participants’ perspectives and avoid exclusion. The discussion highlights tensions between protecting vulnerable groups and ensuring their representation in research critical to public health.